Examining utility and feasibility of implementing patient-reported outcome measures in occupational therapy primary care practice. (July 2022) - Hand, Carri; Donnelly, Catherine; Bobbette, Nicole; Borczyk, Maria; Bauer, Martha; O'Neill, Collen
Introduction: Occupational therapists are increasingly part of interprofessional primary care teams, helping to expand primary care to meet client needs. Effectiveness of occupational therapy services is difficult to determine with currently collected data, and little is known about the best tools to use or how to integrate tools into practice. We explored the utility and feasibility of implementing patient-reported outcome measures (PROMs) within occupational therapy primary care practice. Method: We integrated pre-test/post-test and exploratory qualitative designs. Over 7 months, nine occupational therapists administered two PROMs to clients receiving falls prevention services, addressing falls efficacy and participation in daily occupations. Subsequent interviews with therapists explored the utility and feasibility of using the tools. We assessed pre-to-post change in PROM scores and thematically analyzed interview data. Results: The occupational therapists valued measuring function and participation in daily occupations to inform practice, communicate with team members, and demonstrate effectiveness. The falls efficacy scale appeared to capture change over time and was feasible to implement at pre-test. Conclusion: PROMs appear useful within occupational therapy primary care falls prevention services and can be feasible with attention to administration processes. Further development and testing of PROMs is needed to support occupational therapy primary care practice.